THE SEISMOGRAVITY METHOD OF MINERALOGICAL COMPOSITION EVALUATION - PRODAIVODA, G.; VIRSHYLO, I.; KOZIONOVA, O.; PRODAIVODA, T. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The new method of geological interpretation of seismic and gravity data is proposed. The technique of composition estimation based on the inversion of velocities and gravity anomaly is presented. The applying of method on numerical models is considered.